Accelerating Lean Six Sigma Results : How to Achieve Improvement Excellence in the New Economy - Burton, Terence T., 1950- (Andover J. Ross Publisihng, 2014)
Presents a road map for implementing effective, targeted Lean Six Sigma initiatives. This title provides the proven leadership, business infrastructure, and applications to key strategic areas of the business.
Include Index and Epilogue
Keywords: Six sigma (Quality control standard) -- Total quality management -- Cost control